Hydrogenated nitrile rubber dispersing agent solution, preparation method and application of hydrogenated nitrile rubber dispersing agent solution in conductive paste

By using hydrogenated nitrile rubber dispersant solution and high-pressure homogenization technology, the problem of viscosity rebound in carbon nanotube conductive paste during storage is solved, higher solids content and better processing performance are achieved, and the performance of lithium-ion batteries is improved.

CN119875156APending Publication Date: 2025-04-25青岛超瑞纳米新材料科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510094117.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The viscosity of existing carbon nanotube conductive paste rebounds greatly during storage, resulting in difficulty in improving the solid content and degrading processing performance.

Method used

The hydrogenated nitrile rubber (HNBR) dispersant solution is used to reduce the average molecular weight of HNBR through the synergistic effect of high-pressure homogenization and additives, and improve its dispersion effect and viscosity stability.

Benefits of technology

It significantly improves the dispersion effect and viscosity stability of the conductive paste, achieves higher solid content and better processing performance, reduces the resistivity of the electrode sheet and the internal resistance of the battery cell, and improves the low-temperature performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875156A_ABST
    Figure CN119875156A_ABST
Patent Text Reader

Abstract

The invention relates to a hydrogenated butadiene-acrylonitrile rubber dispersing agent solution, a preparation method and application of the hydrogenated butadiene-acrylonitrile rubber dispersing agent solution in conductive paste. The hydrogenated butadiene-acrylonitrile rubber dispersant solution is composed of a solute, a solvent and an auxiliary agent, hydrogenated butadiene-acrylonitrile rubber is adopted as the solute, and N-methyl pyrrolidone and an organic alcohol amine compound are matched to prepare the dispersant solution, so that the dispersity of a conductive agent and the rheological property of slurry can be remarkably improved in practical application; hNBR can better decompose chain agglomeration under the synergistic effect of organic alcohol amine, the molecule wetting ability is enhanced, and then the conductive particle agglomeration phenomenon is inhibited; the formed dispersing agent not only reduces the internal impedance of the pole piece and improves the electrochemical performance of the battery under the conditions of normal temperature and low temperature, but also effectively reduces the viscosity rebound phenomenon in the pulping and storage processes. On the whole, the dispersant solution can enhance the processability of the slurry while ensuring excellent conductivity, and has good industrial application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogenated nitrile rubber processing, and in particular to a hydrogenated nitrile rubber dispersant solution, a preparation method and application thereof in conductive slurry. Background Art

[0002] Conductive agents play a vital role in lithium-ion batteries. Their main functions include improving the electronic conductivity of electrode materials, building an effective electron transport network, reducing the contact resistance of electrodes, and promoting the infiltration of electrolytes. In lithium batteries, the functions and importance of conductive agents are:

[0003] Improve electronic conductivity: During the charging and discharging process of lithium-ion batteries, electrons need to move quickly in the electrode material to maintain battery performance. The addition of conductive agents significantly improves the electronic conductivity of the electrode, thereby accelerating the migration rate of electrons and reducing the polarization of the battery.

[0004] Constructing an electron transport network: The conductive agent forms a continuous conductive network in the electrode material, ensuring efficient electron transport within the electrode. This network structure is particularly critical for maintaining the performance of the battery under high-rate charge and discharge conditions.

[0005] Reduce contact resistance: Conductive agents accelerate the movement of electrons by reducing the contact resistance between electrode material particles, which is of great significance for improving the charging and discharging efficiency of batteries and extending battery life.

[0006] Promote electrolyte infiltration: The addition of conductive agents can also improve the wettability of the electrolyte to the electrode material, help the migration of lithium ions in the electrode material, and further improve the charge and discharge performance of the battery.

[0007] Improving battery performance: Taking the above functions into consideration, conductive agents have an important impact on improving the energy density, power density, cycle stability and safety of lithium-ion batteries.

[0008] There are many types of conductive agents, including traditional carbon black, conductive graphite, carbon fiber, as well as new carbon nanotubes, graphene, etc. Each conductive agent has its own unique physical and chemical properties and is suitable for different battery systems and application scenarios. The selection and optimization of conductive agents is crucial to improving battery performance and is a key direction in battery material research and development.

[0009] Carbon nanotubes and graphene are new conductive agents that have developed rapidly in recent years. They are increasingly used in lithium batteries because of their excellent conductivity, high mechanical strength, good compatibility, and improved energy density. However, they also face some challenges, such as difficulty in dispersion: due to their special structure and properties, it is difficult to disperse them evenly in the slurry. If they are not dispersed well, their performance may be affected; the slurry viscosity is unstable: due to the large specific surface area of ​​carbon nanotubes, after being dispersed into slurry, the viscosity rebounds greatly, resulting in increased viscosity of the positive electrode and the slurry, which is not conducive to positive electrode coating.

[0010] Traditional carbon nanotube conductive paste and carbon nanotube composite conductive paste are dispersed using PVP as a dispersant. However, the carbon nanotube conductive paste dispersed using PVP has a large viscosity rebound during storage, resulting in the solid content of the conductive paste cannot be increased. At the same time, the processing performance of the conductive paste after the viscosity rebound is reduced in subsequent use. Summary of the invention

[0011] The object of the present invention is to provide a hydrogenated nitrile rubber dispersant solution, a preparation method and application thereof in a conductive slurry, so as to solve the problems raised in the above-mentioned background technology.

[0012] The present invention provides a hydrogenated nitrile rubber dispersant solution consisting of a solute, a solvent and an auxiliary agent.

[0013] The solute is hydrogenated nitrile rubber with a mass average molecular weight of 20,000-200,000;

[0014] The solvent is N-methylpyrrolidone;

[0015] The auxiliary agent is an organic alcohol amine compound. During the preparation process of the hydrogenated nitrile dispersant solution, the auxiliary agent reduces the surface tension, wetting and penetration of the solution, so that the hydrogenated nitrile rubber can be fully dissolved in the NMP solvent; at the same time, the addition of the auxiliary agent can synergize with the hydrogenated nitrile rubber when the hydrogenated nitrile rubber is dispersed in the conductive paste, so that the conductive paste can be better dispersed, the viscosity of the conductive paste is lower, and the stabilizing viscosity effect is more excellent.

[0016] Preferably, the auxiliary agent is a combination of polyether polyol and D-aminopropanol in a mass ratio of 1:(0.2-5), and the preferred mass ratio is 1:(0.5-2).

[0017] Preferably, the hydroxyl value of the polyether polyol is in the range of 20-300 mgKOH / g.

[0018] Preferably, the polyether polyol is C2004, F3056D, C2010D, C2020, C2040D, F3150 and At least one of S3007.

[0019] Preferably, the auxiliary agent is a combination of polyether polyol, polyether surfactant and D-aminopropanol in a mass ratio of 1:(0.2-2):(0.2-2). The polyether surfactant is F68, Pluro F127 and At least one of L64.

[0020] Preferably, the hydrogenated nitrile rubber dispersant solution is composed, by mass percentage, of 1-30% hydrogenated nitrile rubber, 0.1-15% auxiliary agent, and the balance is N-methylpyrrolidone.

[0021] Preferably, the hydrogenated nitrile rubber dispersant solution is composed, by mass percentage, of 8-20% hydrogenated nitrile rubber, 3-10% auxiliary agent, and the balance is N-methylpyrrolidone.

[0022] Preferably, the hydrogenated nitrile rubber has a mass average molecular weight of 40,000 to 100,000.

[0023] The present invention also provides a method for preparing a hydrogenated nitrile rubber dispersant solution, comprising the following steps:

[0024] Mixing hydrogenated nitrile rubber, N-methylpyrrolidone and an additive;

[0025] High pressure homogenization.

[0026] Preferably, a method for preparing a hydrogenated nitrile rubber dispersant solution comprises the following steps:

[0027] S1) cutting hydrogenated nitrile rubber into pieces with a rubber cutting machine;

[0028] S2) adding the chopped hydrogenated nitrile rubber, N-methylpyrrolidone and additives into a stirring tank in proportion, and soaking at 20-28° C. for 1-3 hours;

[0029] S3) stirring at 20-28° C. and 200-1000 rpm for 6-10 hours;

[0030] S4) homogenizing at 20-50° C. and pressure of 40-180 MPa for 2-8 times to obtain the hydrogenated nitrile rubber dispersant solution.

[0031] Preferably, the volume of the hydrogenated nitrile rubber after cutting in step S1 is 0.5-10cm 3 .

[0032] The hydrogenated nitrile rubber (HNBR) dispersant solution prepared by the method of the present invention can appropriately reduce the average molecular weight of HNBR through the synergistic effect of high-pressure homogenization and additives. On the one hand, the decrease in molecular weight enhances the solubility and wetting ability of the rubber in the solvent and significantly improves the dispersion effect; on the other hand, after the viscosity is relatively reduced, it is conducive to the preparation of a conductive paste with a higher solid content, and the viscosity fluctuation is smaller, and the coating and production efficiency are better.

[0033] Preferably, the method further comprises step S5) of demagnetization. The demagnetization step is permanent magnet demagnetization or electric demagnetization, the magnetic intensity of permanent magnet demagnetization is 12000-100000 Gauss, and the magnetic intensity of electric demagnetization is 50000-200000 Gauss. Demagnetizing the solution by permanent magnet or electric demagnetization can effectively reduce the interference of impurities on the quality of the finished product and the electrochemical performance, thereby improving the safety and reliability of the final application.

[0034] The invention also provides an application of a hydrogenated nitrile rubber dispersant solution in a conductive slurry.

[0035] The invention also provides a conductive paste, which consists of a conductive agent, the hydrogenated nitrile rubber dispersant solution and N-methyl pyrrolidone.

[0036] Preferably, the mass content of the conductive agent in the conductive paste is 1.5-15%, and the mass content of the hydrogenated nitrile rubber is 0.2-4%.

[0037] Preferably, the conductive agent is at least one of carbon nanotubes, graphene, conductive carbon black SP, acetylene black and Ketjen black.

[0038] The present invention also provides a method for preparing a conductive paste, comprising the following steps:

[0039] a) stirring the conductive agent, the hydrogenated nitrile rubber dispersant solution and N-methylpyrrolidone in a premixing tank at 200-1000 rpm for 10-30 min;

[0040] b) Sanding, homogenization or ultrasound.

[0041] Preferably, the linear speed of the sand milling in step b is 10-30 m / s; the sand milling in step b is performed 2-8 times; the homogenization pressure is 50-100 Mpa, and the homogenization is performed 2-8 times; the ultrasonic power in step b is 2-8 Kw, and the ultrasonic time is 5-15 min.

[0042] Preferably, the method further comprises step c: demagnetization. The demagnetization step is permanent magnet demagnetization or electric demagnetization, the magnetic intensity of permanent magnet demagnetization is 8000-15000 Gauss, and the background magnetic intensity of electric demagnetization is 10000-20000 Gauss.

[0043] The present invention also provides an application of a conductive slurry in a lithium battery electrode. The conductive slurry of the present invention containing a hydrogenated nitrile rubber composite dispersant is used as a conductive agent for a positive electrode of a lithium battery. When the positive electrode of the lithium battery is slurried, the conductive slurry containing a hydrogenated nitrile rubber composite dispersant is added with a positive electrode active material, a binder, and a solvent in a normal order of addition, and slurry is prepared according to a normal process flow, and then a lithium battery is manufactured according to a conventional lithium battery process.

[0044] The present invention shows significant improvements in specific indicators such as pole piece resistivity, slurry viscosity and its storage stability, battery cell internal resistance, especially low-temperature DCR. Through the high-pressure homogenization and additive superposition process, the molecular weight of hydrogenated nitrile rubber (HNBR) can be moderately reduced, so that the polar groups and additives of the dispersant can cooperate more fully when coating the conductive particles, forming a more uniform electron transmission network, thereby significantly reducing the pole piece resistivity and battery cell internal resistance; at the same time, the rubber elastic structure of HNBR also makes it difficult for the slurry to agglomerate or rebound in viscosity during storage, so that it can maintain a low viscosity for a long time and achieve better coating and processing performance; in addition, the HNBR dispersant can also improve the toughness and adhesion of the pole piece, and also significantly improve the DCR in a low-temperature environment, so that the battery still has higher discharge efficiency and stability under low-temperature conditions such as -10°C.

[0045] Compared with the prior art, the present invention has the following technical effects:

[0046] 1) The modified hydrogenated nitrile rubber dispersant solution has better processing performance;

[0047] 2) The conductive paste of the present invention has better conductivity, viscosity stability, processing performance and high production efficiency;

[0048] 3) The conductive slurry dispersed with the hydrogenated nitrile rubber dispersant solution of the present invention has been verified through actual application in batteries. The internal resistance of the battery cell can be reduced by 8-10%, the adhesion of the electrode can be increased by more than 300%, the toughness of the electrode can be greatly improved, and the rate performance and low temperature performance of the battery cell can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 It is a process diagram for preparing hydrogenated nitrile rubber (HNBR) dispersant solution;

[0050] Figure 2 The figure is a preparation process diagram of a conductive paste containing a hydrogenated nitrile rubber (HNBR) composite dispersant. DETAILED DESCRIPTION

[0051] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0052] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments.

[0053] In the following examples and comparative examples, unless otherwise specified, the additives used are: polyether polyol (Wanhua Chemical An auxiliary agent obtained by mixing C2020 polyether polyol, hydroxyl value 56 mgKOH / g) with D-aminopropanol in a mass ratio of 1:1.

[0054] Example 1

[0055] In this embodiment, a method for preparing a hydrogenated nitrile rubber (HNBR) dispersant solution is carried out according to the following steps. Figure 1 :

[0056] Step 1) selecting hydrogenated nitrile rubber with a mass average molecular weight of 200,000 and cutting it into small pieces of 8 cubic centimeters in volume using a rubber cutting machine;

[0057] Step 2) HNBR, NMP and additives cut into small pieces are mixed in a mass ratio of 1:98.9:0.1, added to a stirring tank, and the HNBR is immersed in the liquid at 25° C. for 2 hours;

[0058] Step 3) stirring the mixture after step 2 at 25°C and 500 rpm for 8 hours;

[0059] Step 4) homogenizing the mixed material after step 3, at 40° C. and a homogenization pressure of 60 MPa, for 5 times to obtain a hydrogenated nitrile rubber (HNBR) composite dispersant solution;

[0060] Step 5) demagnetizing the hydrogenated nitrile rubber (HNBR) composite dispersant solution after step 4, controlling the magnetic intensity of the permanent magnet demagnetization to 15000 Gauss, to obtain a hydrogenated nitrile rubber (HNBR) composite dispersant solution;

[0061] Step 6) The hydrogenated nitrile rubber (HNBR) composite dispersant solution is sealed and canned to obtain a finished solution, which is recorded as hydrogenated nitrile rubber (HNBR) composite dispersant 1.

[0062] Example 2

[0063] The preparation method of a hydrogenated nitrile rubber (HNBR) composite dispersant solution in this embodiment is carried out according to the following steps:

[0064] Step 1) selecting hydrogenated nitrile rubber with a mass average molecular weight of 200,000 and cutting it into small pieces of 8 cubic centimeters in volume using a rubber cutting machine;

[0065] Step 2) HNBR, NMP and additives cut into small pieces are mixed in a mass ratio of 8:89:3, added to a stirring tank, and the HNBR is immersed in the liquid at 25° C. for 2 hours;

[0066] Step 3) stirring the mixture after step 2 at 25°C and 500 rpm for 8 hours;

[0067] Step 4) homogenizing the mixed material after step 3, at 40° C. and a homogenization pressure of 80 MPa, for 5 times to obtain a hydrogenated nitrile rubber (HNBR) composite dispersant solution;

[0068] Step 5) demagnetizing the hydrogenated nitrile rubber (HNBR) composite dispersant solution after step 4, controlling the magnetic intensity of the permanent magnet demagnetization to 15000 Gauss, to obtain a hydrogenated nitrile rubber (HNBR) composite dispersant solution;

[0069] Step 6) The hydrogenated nitrile rubber (HNBR) composite dispersant solution is sealed and canned to obtain a finished solution, which is recorded as hydrogenated nitrile rubber (HNBR) composite dispersant 2.

[0070] Example 3

[0071] The preparation method of a hydrogenated nitrile rubber (HNBR) dispersant solution in this embodiment is carried out according to the following steps:

[0072] Step 1) selecting hydrogenated nitrile rubber with a mass average molecular weight of 200,000 and cutting it into small pieces of 8 cubic centimeters in volume using a rubber cutting machine;

[0073] Step 2) HNBR, NMP and additives cut into small pieces are mixed in a mass ratio of 10:85:5, added to a stirring tank, and the HNBR is immersed in the liquid at 25° C. for 2 hours;

[0074] Step 3) stirring the mixture after step 2 at 25°C and 500 rpm for 8 hours;

[0075] Step 4) homogenizing the mixed material after step 3, at 40° C. and a homogenization pressure of 110 MPa, for 5 times to obtain a hydrogenated nitrile rubber (HNBR) composite dispersant solution;

[0076] Step 5) demagnetizing the hydrogenated nitrile rubber (HNBR) composite dispersant solution after step 4, controlling the magnetic intensity of the permanent magnet demagnetization to 15000 Gauss, to obtain a hydrogenated nitrile rubber (HNBR) composite dispersant solution;

[0077] Step 6) The hydrogenated nitrile rubber (HNBR) composite dispersant solution is sealed and canned to obtain a finished solution, which is recorded as hydrogenated nitrile rubber (HNBR) composite dispersant 3.

[0078] Example 4

[0079] The preparation method of a hydrogenated nitrile rubber (HNBR) dispersant solution in this embodiment is carried out according to the following steps:

[0080] Step 1) selecting hydrogenated nitrile rubber with a mass average molecular weight of 200,000 and cutting it into small pieces of 8 cubic centimeters in volume using a rubber cutting machine;

[0081] Step 2) HNBR, NMP and additives cut into small pieces are mixed in a mass ratio of 12:83:5, added to a stirring tank, and the HNBR is immersed in the liquid at 25° C. for 2 hours;

[0082] Step 3) stirring the mixture after step 2 at 25°C and 500 rpm for 8 hours;

[0083] Step 4) homogenizing the mixed material after step 3, at 40° C. and a homogenization pressure of 140 MPa, for 5 times to obtain a hydrogenated nitrile rubber (HNBR) composite dispersant solution;

[0084] Step 5) demagnetizing the hydrogenated nitrile rubber (HNBR) composite dispersant solution after step 4, controlling the magnetic intensity of the permanent magnet demagnetization to 15000 Gauss, to obtain a hydrogenated nitrile rubber (HNBR) composite dispersant solution;

[0085] Step 6) The hydrogenated nitrile rubber (HNBR) composite dispersant solution is sealed and canned to obtain a finished solution, which is recorded as hydrogenated nitrile rubber (HNBR) composite dispersant 4.

[0086] Example 5

[0087] The preparation method of a hydrogenated nitrile rubber (HNBR) dispersant solution in this embodiment is carried out according to the following steps:

[0088] Step 1) selecting hydrogenated nitrile rubber with a mass average molecular weight of 200,000 and cutting it into small pieces of 8 cubic centimeters in volume using a rubber cutting machine;

[0089] Step 2) HNBR, NMP and additives cut into small pieces are mixed in a mass ratio of 12:82:6, added to a stirring tank, and the HNBR is immersed in the liquid at 25° C. for 2 hours;

[0090] Step 3) stirring the mixture after step 2 at 25°C and 500 rpm for 8 hours;

[0091] Step 4) homogenizing the mixed material after step 3, at 40° C. and a homogenization pressure of 170 MPa, for 5 times to obtain a hydrogenated nitrile rubber (HNBR) composite dispersant solution;

[0092] Step 5) demagnetizing the hydrogenated nitrile rubber (HNBR) composite dispersant solution after step 4, controlling the magnetic intensity of the permanent magnet demagnetization to 15000 Gauss, to obtain a hydrogenated nitrile rubber (HNBR) composite dispersant solution;

[0093] Step 6) The hydrogenated nitrile rubber (HNBR) composite dispersant solution is sealed and canned to obtain a finished solution, which is recorded as hydrogenated nitrile rubber (HNBR) composite dispersant 5.

[0094] Example 6

[0095] The preparation method of a hydrogenated nitrile rubber (HNBR) dispersant solution in this embodiment is carried out according to the following steps:

[0096] Step 1) selecting hydrogenated nitrile rubber with a mass average molecular weight of 100,000 and cutting it into small pieces of 8 cubic centimeters in volume using a rubber cutting machine;

[0097] Step 2) HNBR, NMP and additives cut into small pieces are mixed in a mass ratio of 10:85:5, added to a stirring tank, and the HNBR is immersed in the liquid at 25° C. for 2 hours;

[0098] Step 3) stirring the mixture after step 2 at 25°C and 500 rpm for 8 hours;

[0099] Step 4) homogenizing the mixed material after step 3, at 40° C. and a homogenization pressure of 60 MPa, for 5 times to obtain a hydrogenated nitrile rubber (HNBR) composite dispersant solution;

[0100] Step 5) demagnetizing the hydrogenated nitrile rubber (HNBR) composite dispersant solution after step 4, controlling the magnetic intensity of the permanent magnet demagnetization to 15000 Gauss, to obtain a hydrogenated nitrile rubber (HNBR) composite dispersant solution;

[0101] Step 6) The hydrogenated nitrile rubber (HNBR) composite dispersant solution is sealed and canned to obtain a finished solution, which is recorded as hydrogenated nitrile rubber (HNBR) composite dispersant 6.

[0102] Example 7

[0103] The preparation method of a hydrogenated nitrile rubber (HNBR) dispersant solution in this embodiment is carried out according to the following steps:

[0104] Step 1) selecting hydrogenated nitrile rubber with a mass average molecular weight of 100,000 and cutting it into small pieces of 8 cubic centimeters in volume using a rubber cutting machine;

[0105] Step 2) HNBR, NMP and additives cut into small pieces are mixed in a mass ratio of 15:78:7, added to a stirring tank, and the HNBR is immersed in the liquid at 25° C. for 2 hours;

[0106] Step 3) stirring the mixture after step 2 at 25°C and 500 rpm for 8 hours;

[0107] Step 4) homogenizing the mixed material after step 3, at 40° C. and a homogenization pressure of 80 MPa, for 5 times to obtain a hydrogenated nitrile rubber (HNBR) composite dispersant solution;

[0108] Step 5) demagnetizing the hydrogenated nitrile rubber (HNBR) composite dispersant solution after step 4, controlling the magnetic intensity of the permanent magnet demagnetization to 15000 Gauss, to obtain a hydrogenated nitrile rubber (HNBR) composite dispersant solution;

[0109] Step 6) The hydrogenated nitrile rubber (HNBR) composite dispersant solution is sealed and canned to obtain a finished solution, which is recorded as hydrogenated nitrile rubber (HNBR) composite dispersant 7.

[0110] Example 8

[0111] The preparation method of a hydrogenated nitrile rubber (HNBR) dispersant solution in this embodiment is carried out according to the following steps:

[0112] Step 1) selecting hydrogenated nitrile rubber with a mass average molecular weight of 100,000 and cutting it into small pieces of 8 cubic centimeters in volume using a rubber cutting machine;

[0113] Step 2) HNBR, NMP and additives cut into small pieces are mixed in a mass ratio of 20:72:8, added to a stirring tank, and the HNBR is immersed in the liquid at 25° C. for 2 hours;

[0114] Step 3) stirring the mixture after step 2 at 25°C and 500 rpm for 8 hours;

[0115] Step 4) homogenizing the mixed material after step 3, at 40° C. and a homogenization pressure of 110 MPa, for 5 times to obtain a hydrogenated nitrile rubber (HNBR) composite dispersant solution;

[0116] Step 5) demagnetizing the hydrogenated nitrile rubber (HNBR) composite dispersant solution after step 4, controlling the magnetic intensity of the permanent magnet demagnetization to 15000 Gauss, to obtain a hydrogenated nitrile rubber (HNBR) composite dispersant solution;

[0117] Step 6) The hydrogenated nitrile rubber (HNBR) composite dispersant solution is sealed and canned to obtain a finished solution, which is recorded as hydrogenated nitrile rubber (HNBR) composite dispersant 8.

[0118] Example 9

[0119] The preparation method of a hydrogenated nitrile rubber (HNBR) dispersant solution in this embodiment is carried out according to the following steps:

[0120] Step 1) selecting hydrogenated nitrile rubber with a mass average molecular weight of 100,000 and cutting it into small pieces of 8 cubic centimeters in volume using a rubber cutting machine;

[0121] Step 2) HNBR, NMP and additives cut into small pieces are mixed in a mass ratio of 25:63:12, added to a stirring tank, and the HNBR is immersed in the liquid at 25° C. for 2 hours;

[0122] Step 3) stirring the mixture after step 2 at 25°C and 500 rpm for 8 hours;

[0123] Step 4) homogenizing the mixed material after step 3, at 40° C. and a homogenization pressure of 140 MPa, for 5 times to obtain a hydrogenated nitrile rubber (HNBR) composite dispersant solution,

[0124] Step 5) demagnetizing the hydrogenated nitrile rubber (HNBR) composite dispersant solution after step 4, controlling the magnetic intensity of the permanent magnet demagnetization to 15000 Gauss, to obtain a hydrogenated nitrile rubber (HNBR) composite dispersant solution;

[0125] Step 6) The hydrogenated nitrile rubber (HNBR) composite dispersant solution is sealed and canned to obtain a finished solution, which is recorded as hydrogenated nitrile rubber (HNBR) composite dispersant 9.

[0126] Example 10

[0127] The preparation method of a hydrogenated nitrile rubber (HNBR) dispersant solution in this embodiment is carried out according to the following steps:

[0128] Step 1) selecting hydrogenated nitrile rubber with a mass average molecular weight of 100,000 and cutting it into small pieces of 8 cubic centimeters in volume using a rubber cutting machine;

[0129] Step 2) HNBR, NMP and additives cut into small pieces are mixed in a mass ratio of 30:55:15, added to a stirring tank, and the HNBR is immersed in the liquid at 25° C. for 2 hours;

[0130] Step 3) stirring the mixture after step 2 at 25°C and 500 rpm for 8 hours;

[0131] Step 4) Homogenize the mixture after step 3 at 40°C and a homogenization pressure of 140 MPa for 5 times

[0132] Step 5) demagnetizing the hydrogenated nitrile rubber (HNBR) composite dispersant solution after step 4, controlling the magnetic intensity of the permanent magnet demagnetization to 15000 Gauss, to obtain a hydrogenated nitrile rubber (HNBR) composite dispersant solution;

[0133] Step 6) The hydrogenated nitrile rubber (HNBR) composite dispersant solution is sealed and canned to obtain a finished solution, which is recorded as hydrogenated nitrile rubber (HNBR) composite dispersant 10.

[0134] Group Hydrogenated Nitrile Dispersant Solution No. Hydrogenated nitrile rubber mass average molecular weight raw material 20W Hydrogenated Nitrile Rubber (HNBR) 216,000 Example 1 Hydrogenated nitrile rubber (HNBR) composite dispersant 1 178,000 Example 2 Hydrogenated nitrile rubber (HNBR) composite dispersant 2 145,000 Example 3 Hydrogenated nitrile rubber (HNBR) composite dispersant 3 125,000 Example 4 Hydrogenated nitrile rubber (HNBR) composite dispersant 4 111,000 Example 5 Hydrogenated nitrile rubber (HNBR) composite dispersant 5 102,000 raw material 10W Hydrogenated Nitrile Rubber (HNBR) 112,000 Example 6 Hydrogenated nitrile rubber (HNBR) composite dispersant 6 89,000 Example 7 Hydrogenated nitrile rubber (HNBR) composite dispersant 7 75,000 Example 8 Hydrogenated nitrile rubber (HNBR) composite dispersant 8 65,000 Example 9 Hydrogenated nitrile rubber (HNBR) composite dispersant 9 57,000 Example 10 Hydrogenated nitrile rubber (HNBR) composite dispersant 10 52,000

[0135] The relevant data of the hydrogenated nitrile rubber (HNBR) composite dispersant obtained in the above examples are shown in the above table. The examples can prove that the method of the present invention is used to prepare the hydrogenated nitrile rubber (HNBR) composite dispersant, which can reduce the molecular weight of the hydrogenated nitrile rubber in the composite dispersant so as to better disperse the conductive paste.

[0136] Embodiment 11

[0137] Preparation and application of a conductive paste containing a hydrogenated nitrile rubber (HNBR) composite dispersant, see Figure 2 .

[0138] Step S1) The specific surface area is 320m 2 / g carbon nanotube powder, hydrogenated nitrile rubber (HNBR) composite dispersant 1, and NMP are added into a premixing tank at a ratio of CNT:HNBR:NMP=3.2:0.65:96.15, and the actual amount of NMP added is deducted from the non-solute portion of the hydrogenated nitrile rubber (HNBR) composite dispersant solution added;

[0139] Step S2) stirring at 750 rpm for 20 minutes at room temperature in a premixing tank;

[0140] Step S3) The mixed materials are pre-mixed sufficiently and then sand-milled. The linear speed of the sand-milling dispersion rotor is 15 m / s and the sand-milling is repeated 4 times.

[0141] Step S4) After the sand-grinded slurry has fluidity, the slurry is homogenized at a homogenization pressure of 50 MPa for 5 times;

[0142] Step S5) After homogenization, the slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0143] The finished conductive slurry containing hydrogenated nitrile rubber composite dispersant is used as the positive electrode conductive agent of the lithium-ion battery to make the lithium-ion aluminum shell battery. The specific preparation method is as follows:

[0144] 1) Lithium-ion battery positive electrode formula, by mass ratio, lithium iron phosphate active material: conductive paste prepared in this embodiment: PVDF binder = 98%: 0.5%: 1.5%;

[0145] 2) Lithium-ion battery negative electrode matching method, by mass ratio, graphite active material: CMC: SBR binder = 96.5%: 1.5%: 2%;

[0146] 3) Prepare positive electrode slurry according to the positive electrode formula, apply the prepared positive electrode slurry on aluminum foil with a thickness of 20 μm, control the wet film thickness to 100 μm, dry and roll to obtain positive electrode sheet, and test the resistivity of the positive electrode sheet by four-probe method and record the data;

[0147] 4) preparing negative electrode slurry according to the negative electrode formula, coating the prepared negative electrode slurry on a copper foil with a thickness of 10 μm, controlling the wet film thickness to 80 μm, and drying and rolling to obtain a negative electrode sheet;

[0148] 5) The positive electrode sheet, negative electrode sheet, isolation membrane, electrolyte (1 mol / L LiPF6 lithium hexafluorophosphate dissolved in a mixed solvent of EC ethylene carbonate, DMC dimethyl carbonate and EMC ethyl methyl carbonate in a volume ratio of 1:1:1) and other battery materials are made into aluminum shell batteries according to the normal battery process, the N / P ratio is controlled at 1.08, and the electrochemical performance test is carried out according to the normal process flow of lithium-ion batteries, and the battery internal resistance test results and -10℃ battery DCR test results are recorded.

[0149] Example 12

[0150] The preparation and application of a conductive paste containing a hydrogenated nitrile rubber (HNBR) composite dispersant are as follows:

[0151] Step S1) The specific surface area is 320m 2 / g carbon nanotube powder, hydrogenated nitrile rubber (HNBR) composite dispersant 2, and NMP are added into a premixing tank at a ratio of CNT:HNBR:NMP=3.2:0.65:96.15, and the actual amount of NMP added is deducted from the non-solute portion of the hydrogenated nitrile rubber (HNBR) composite dispersant solution added;

[0152] Step S2) stirring at 750 rpm for 20 minutes at room temperature in a premixing tank;

[0153] Step S3) The mixed materials are pre-mixed sufficiently and then sand-milled. The linear speed of the sand-milling dispersion rotor is 15 m / s and the sand-milling is repeated 4 times.

[0154] Step S4) After the sand-grinded slurry has fluidity, the slurry is homogenized at a homogenization pressure of 80 MPa for 5 times;

[0155] Step S5) After homogenization, the slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0156] The finished conductive slurry containing hydrogenated nitrile rubber composite dispersant is used as the positive electrode conductive agent of the lithium ion battery cell to make the lithium ion aluminum shell battery cell. The specific method is carried out by referring to the relevant method of Example 11.

[0157] Example 13

[0158] The preparation and application of a conductive paste containing a hydrogenated nitrile rubber (HNBR) composite dispersant are as follows:

[0159] Step S1) The specific surface area is 320m 2 / g carbon nanotube powder, hydrogenated nitrile rubber (HNBR) composite dispersant 3, NMP in the premixing tank at a ratio of CNT:HNBR:NMP=3.2:0.65:96.15, the actual amount of NMP added is deducted from the non-solute portion of the hydrogenated nitrile rubber (HNBR) composite dispersant solution added;

[0160] Step S2) stirring at 750 rpm for 20 minutes at room temperature in a premixing tank;

[0161] Step S3) The mixed materials are pre-mixed sufficiently and then sand-milled. The linear speed of the sand-milling dispersion rotor is 15 m / s and the sand-milling is repeated 4 times.

[0162] Step S4) After the sand-grinded slurry has fluidity, the slurry is homogenized at a homogenization pressure of 80 MPa for 5 times;

[0163] Step S5) After homogenization, the slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0164] The finished conductive slurry containing hydrogenated nitrile rubber composite dispersant is used as the positive electrode conductive agent of the lithium ion battery cell to make the lithium ion aluminum shell battery cell. The specific method is carried out by referring to the relevant method of Example 11.

[0165] Embodiment 14

[0166] The preparation and application of a conductive paste containing a hydrogenated nitrile rubber (HNBR) composite dispersant are as follows:

[0167] Step S1) The specific surface area is 320m 2 / g carbon nanotube powder, hydrogenated nitrile rubber (HNBR) composite dispersant 4, NMP in the premixing tank at a ratio of CNT:HNBR:NMP = 3.2:0.65:96.15, the actual amount of NMP added is deducted from the non-solute portion of the hydrogenated nitrile rubber (HNBR) composite dispersant solution;

[0168] Step S2) stirring at 750 rpm for 20 minutes at room temperature in a premixing tank;

[0169] Step S3) The mixed materials are pre-mixed sufficiently and then sand-milled. The linear speed of the sand-milling dispersion rotor is 15 m / s and the sand-milling is repeated 4 times.

[0170] Step S4) After the sand-grinded slurry has fluidity, the slurry is homogenized at a homogenization pressure of 100 MPa for 5 times;

[0171] Step S5) After homogenization, the slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0172] The finished conductive slurry containing hydrogenated nitrile rubber composite dispersant is used as the positive electrode conductive agent of the lithium ion battery cell to make the lithium ion aluminum shell battery cell. The specific method is carried out by referring to the relevant method of Example 11.

[0173] Embodiment 15

[0174] The preparation and application of a conductive paste containing a hydrogenated nitrile rubber (HNBR) composite dispersant are as follows:

[0175] Step S1) The specific surface area is 320m 2 / g carbon nanotube powder, hydrogenated nitrile rubber (HNBR) composite dispersant 5, NMP in the premixing tank at a ratio of CNT:HNBR:NMP=3.2:0.65:96.15, the actual amount of NMP added is deducted from the non-solute portion of the hydrogenated nitrile rubber (HNBR) composite dispersant solution;

[0176] Step S2) stirring at 750 rpm for 20 minutes at room temperature in a premixing tank;

[0177] Step S3) The mixed materials are pre-mixed sufficiently and then sand-milled. The linear speed of the sand-milling dispersion rotor is 15 m / s and the sand-milling is repeated 4 times.

[0178] Step S4) After the sand-grinded slurry has fluidity, the slurry is homogenized at a homogenization pressure of 120 MPa and a homogenization time of 5 times;

[0179] Step S5) After homogenization, the slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0180] The finished conductive slurry containing hydrogenated nitrile rubber composite dispersant is used as the positive electrode conductive agent of the lithium ion battery cell to make the lithium ion aluminum shell battery cell. The specific method is carried out by referring to the relevant method of Example 11.

[0181] Example 16

[0182] The preparation and application of a conductive paste containing a hydrogenated nitrile rubber (HNBR) composite dispersant are as follows:

[0183] Step S1) feeding carbon nanotube powder with a specific surface area of ​​320 m2 / g, hydrogenated nitrile rubber (HNBR) composite dispersant 6, and NMP in a premixing tank at a ratio of CNT:HNBR:NMP=3.2:0.65:96.15, wherein the actual amount of NMP fed is deducted from the non-solute portion of the hydrogenated nitrile rubber (HNBR) composite dispersant solution fed;

[0184] Step S2) stirring at 750 rpm for 20 minutes at room temperature in a premixing tank;

[0185] Step S3) The mixed materials are pre-mixed sufficiently and then sand-milled. The linear speed of the sand-milling dispersion rotor is 15 m / s and the sand-milling is repeated 4 times.

[0186] Step S4) After the sand-grinded slurry has fluidity, the slurry is homogenized at a homogenization pressure of 60 MPa for 5 times;

[0187] Step S5) After homogenization, the slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0188] The finished conductive slurry containing hydrogenated nitrile rubber composite dispersant is used as the positive electrode conductive agent of the lithium ion battery cell to make the lithium ion aluminum shell battery cell. The specific method is carried out by referring to the relevant method of Example 11.

[0189] Embodiment 17

[0190] The preparation and application of a conductive paste containing a hydrogenated nitrile rubber (HNBR) composite dispersant are as follows:

[0191] Step S1) The specific surface area is 320m 2 / g carbon nanotube powder, hydrogenated nitrile rubber (HNBR) composite dispersant 7, NMP in the premixing tank at a ratio of CNT:HNBR:NMP = 3.2:0.65:96.15, the actual amount of NMP added is deducted from the non-solute portion of the hydrogenated nitrile rubber (HNBR) composite dispersant solution;

[0192] Step S2) stirring at 750 rpm for 20 minutes at room temperature in a premixing tank;

[0193] Step S3) The mixed materials are pre-mixed sufficiently and then sand-milled. The linear speed of the sand-milling dispersion rotor is 15 m / s and the sand-milling is repeated 4 times.

[0194] Step S4) After the sand-grinded slurry has fluidity, the slurry is homogenized at a homogenization pressure of 100 MPa for 5 times;

[0195] Step S5) After homogenization, the slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0196] The finished conductive slurry containing hydrogenated nitrile rubber composite dispersant is used as the positive electrode conductive agent of the lithium ion battery cell to make the lithium ion aluminum shell battery cell. The specific method is carried out by referring to the relevant method of Example 11.

[0197] Embodiment 18

[0198] The preparation and application of a conductive paste containing a hydrogenated nitrile rubber (HNBR) composite dispersant are as follows:

[0199] Step S1) The specific surface area is 320m 2 / g carbon nanotube powder, hydrogenated nitrile rubber (HNBR) composite dispersant 8, and NMP are added into a premixing tank at a ratio of CNT:HNBR:NMP=3.2:0.65:96.15. The actual amount of NMP added is deducted from the non-solute portion of the hydrogenated nitrile rubber (HNBR) composite dispersant solution added;

[0200] Step S2) stirring at 750 rpm for 20 minutes at room temperature in a premixing tank;

[0201] Step S3) The mixed materials are pre-mixed sufficiently and then sand-milled. The linear speed of the sand-milling dispersion rotor is 15 m / s and the sand-milling is repeated 4 times.

[0202] Step S4) After the sand-grinded slurry has fluidity, the slurry is homogenized at a homogenization pressure of 100 MPa for 5 times;

[0203] Step S5) After homogenization, the slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0204] The finished conductive slurry containing hydrogenated nitrile rubber composite dispersant is used as the positive electrode conductive agent of the lithium ion battery cell to make the lithium ion aluminum shell battery cell. The specific method is carried out by referring to the relevant method of Example 11.

[0205] Embodiment 19

[0206] The preparation and application of a conductive paste containing a hydrogenated nitrile rubber (HNBR) composite dispersant are as follows:

[0207] Step S1) The specific surface area is 320m 2 / g carbon nanotube powder, hydrogenated nitrile rubber (HNBR) composite dispersant 9, and NMP are added into a premixing tank at a ratio of CNT:HNBR:NMP=3.2:0.65:96.15, and the actual amount of NMP added is deducted from the non-solute portion of the hydrogenated nitrile rubber (HNBR) composite dispersant solution added;

[0208] Step S2) stirring at 750 rpm for 20 minutes at room temperature in a premixing tank;

[0209] Step S3) The mixed materials are pre-mixed sufficiently and then sand-milled. The linear speed of the sand-milling dispersion rotor is 15 m / s and the sand-milling is repeated 4 times.

[0210] Step S4) After the sand-grinded slurry has fluidity, the slurry is homogenized at a homogenization pressure of 80 MPa and a homogenization time of 5 times;

[0211] Step S5) After homogenization, the slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0212] The finished conductive slurry containing hydrogenated nitrile rubber composite dispersant is used as the positive electrode conductive agent of the lithium ion battery cell to make the lithium ion aluminum shell battery cell. The specific method is carried out by referring to the relevant method of Example 11.

[0213] Embodiment 20

[0214] The preparation and application of a conductive paste containing a hydrogenated nitrile rubber (HNBR) composite dispersant are as follows:

[0215] Step S1) The specific surface area is 320m 2 / g carbon nanotube powder, hydrogenated nitrile rubber (HNBR) composite dispersant 10, and NMP are added into a premixing tank at a ratio of CNT:HNBR:NMP=3.2:0.65:96.15, and the actual amount of NMP added is deducted from the non-solute portion of the hydrogenated nitrile rubber (HNBR) composite dispersant solution added;

[0216] Step S2) stirring at 750 rpm for 20 minutes at room temperature in a premixing tank;

[0217] Step S3) The mixed materials are pre-mixed sufficiently and then sand-milled. The linear speed of the sand-milling dispersion rotor is 15 m / s and the sand-milling is repeated 4 times.

[0218] Step S4) After the sand-grinded slurry has fluidity, the slurry is homogenized at a homogenization pressure of 80 MPa for 5 times;

[0219] Step S5) After homogenization, the slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0220] The finished conductive slurry containing hydrogenated nitrile rubber composite dispersant is used as the positive electrode conductive agent of the lithium ion battery cell to make the lithium ion aluminum shell battery cell. The specific method is carried out by referring to the relevant method of Example 11.

[0221] Embodiment 21

[0222] The preparation and application of a conductive paste containing a hydrogenated nitrile rubber (HNBR) composite dispersant are as follows:

[0223] Step S1) The specific surface area is 240m 2 / g carbon nanotube powder, hydrogenated nitrile rubber (HNBR) composite dispersant 1, and NMP are added into a premixing tank at a ratio of CNT:HNBR:NMP=6.5:1.3:92.2. The actual amount of NMP added is deducted from the non-solute portion of the hydrogenated nitrile rubber (HNBR) composite dispersant solution added;

[0224] Step S2) stirring at 750 rpm for 20 minutes at room temperature in a premixing tank;

[0225] Step S3) The mixed materials are pre-mixed sufficiently and then sand-milled, the linear speed of the sand-milling dispersion rotor is 15 / s, and the sand-milling is performed 4 times;

[0226] Step S4) After the sand-grinded slurry has fluidity, the slurry is homogenized at a homogenization pressure of 50 MPa for 5 times;

[0227] Step S5) After homogenization, the slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0228] The finished conductive slurry containing hydrogenated nitrile rubber composite dispersant is used as the positive electrode conductive agent of the lithium ion battery cell to make the lithium ion aluminum shell battery cell. The specific method is carried out by referring to the relevant method of Example 11.

[0229] Embodiment 22

[0230] The preparation and application of a conductive paste containing a hydrogenated nitrile rubber (HNBR) composite dispersant are as follows:

[0231] Step S1) The specific surface area is 240m 2 / g carbon nanotube powder, hydrogenated nitrile rubber (HNBR) composite dispersant 2, and NMP are added into a premixing tank at a ratio of CNT:HNBR:NMP=6.5:1.3:92.2. The actual amount of NMP added is deducted from the non-solute portion of the hydrogenated nitrile rubber (HNBR) composite dispersant solution added;

[0232] Step S2) stirring at 750 rpm for 20 minutes at room temperature in a premixing tank;

[0233] Step S3) The mixed materials are pre-mixed sufficiently and then sand-milled. The linear speed of the sand-milling dispersion rotor is 15 m / s and the sand-milling is repeated 4 times.

[0234] Step S4) After the sand-grinded slurry has fluidity, the slurry is homogenized at a homogenization pressure of 50 MPa for 5 times;

[0235] Step S5) After homogenization, the slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0236] The finished conductive slurry containing hydrogenated nitrile rubber composite dispersant is used as the positive electrode conductive agent of the lithium ion battery cell to make the lithium ion aluminum shell battery cell. The specific method is carried out by referring to the relevant method of Example 11.

[0237] Embodiment 23

[0238] The preparation and application of a conductive paste containing a hydrogenated nitrile rubber (HNBR) composite dispersant are as follows:

[0239] Step S1) The specific surface area is 240m 2 / g carbon nanotube powder, hydrogenated nitrile rubber (HNBR) composite dispersant 3, NMP are added into the premixing tank at a ratio of CNT:HNBR:NMP=6.5:1.3:92.2, and the actual amount of NMP added is deducted from the non-solute portion of the hydrogenated nitrile rubber (HNBR) composite dispersant solution;

[0240] Step S2) stirring at 750 rpm for 20 minutes at room temperature in a premixing tank;

[0241] Step S3) The mixed materials are pre-mixed sufficiently and then sand-milled. The linear speed of the sand-milling dispersion rotor is 15 m / s and the sand-milling is repeated 4 times.

[0242] Step S4) After the sand-grinded slurry has fluidity, the slurry is homogenized at a homogenization pressure of 80 MPa for 5 times;

[0243] Step S5) After homogenization, the slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0244] The finished conductive slurry containing hydrogenated nitrile rubber composite dispersant is used as the positive electrode conductive agent of the lithium ion battery cell to make the lithium ion aluminum shell battery cell. The specific method is carried out by referring to the relevant method of Example 11.

[0245] Embodiment 24

[0246] The preparation and application of a conductive paste containing a hydrogenated nitrile rubber (HNBR) composite dispersant are as follows:

[0247] Step S1) The specific surface area is 240m 2 / g carbon nanotube powder, hydrogenated nitrile rubber (HNBR) composite dispersant 4, NMP are added into the premixing tank at a ratio of CNT:HNBR:NMP=6.5:1.3:92.2, and the actual amount of NMP added is deducted from the non-solute portion of the hydrogenated nitrile rubber (HNBR) composite dispersant solution;

[0248] Step S2) stirring at 750 rpm for 20 minutes at room temperature in a premixing tank;

[0249] Step S3) the mixed materials are pre-mixed sufficiently and then sand-milled, the linear speed of the sand-milling dispersion rotor is 150 m / s, and the sand-milling is performed 4 times;

[0250] Step S4) After the sand-grinded slurry has fluidity, the slurry is homogenized at a homogenization pressure of 50 MPa for 5 times;

[0251] Step S5) After homogenization, the slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0252] The finished conductive slurry containing hydrogenated nitrile rubber composite dispersant is used as the positive electrode conductive agent of the lithium ion battery cell to make the lithium ion aluminum shell battery cell. The specific method is carried out by referring to the relevant method of Example 11.

[0253] Embodiment 25

[0254] The preparation and application of a conductive paste containing a hydrogenated nitrile rubber (HNBR) composite dispersant are as follows:

[0255] Step S1) The specific surface area is 240m 2 / g carbon nanotube powder, hydrogenated nitrile rubber (HNBR) composite dispersant 5, NMP in the premixing tank at a ratio of CNT:HNBR:NMP=6.5:1.3:92.2, the actual amount of NMP added is deducted from the non-solute portion of the hydrogenated nitrile rubber (HNBR) composite dispersant solution;

[0256] Step S2) stirring at 750 rpm for 20 minutes at room temperature in a premixing tank;

[0257] Step S3) The mixed materials are pre-mixed sufficiently and then sand-milled. The linear speed of the sand-milling dispersion rotor is 15 m / s and the sand-milling is repeated 4 times.

[0258] Step S4) After the sand-grinded slurry has fluidity, the slurry is homogenized at a homogenization pressure of 120 MPa for 5 times;

[0259] Step S5) After homogenization, the slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0260] The finished conductive slurry containing hydrogenated nitrile rubber composite dispersant is used as the positive electrode conductive agent of the lithium ion battery cell to make the lithium ion aluminum shell battery cell. The specific method is carried out by referring to the relevant method of Example 11.

[0261] Embodiment 26

[0262] The preparation and application of a conductive paste containing a hydrogenated nitrile rubber (HNBR) composite dispersant are as follows:

[0263] Step S1) The specific surface area is 240m 2 / g carbon nanotube powder, hydrogenated nitrile rubber (HNBR) composite dispersant 6, NMP are added into the premixing tank at a ratio of CNT:HNBR:NMP=6.5:1.3:92.2, and the actual amount of NMP added is deducted from the non-solute portion of the hydrogenated nitrile rubber (HNBR) composite dispersant solution;

[0264] Step S2) stirring at 750 rpm for 20 minutes at room temperature in a premixing tank;

[0265] Step S3) The mixed materials are pre-mixed sufficiently and then sand-milled. The linear speed of the sand-milling dispersion rotor is 15 m / s and the sand-milling is repeated 4 times.

[0266] Step S4) After the sand-grinded slurry has fluidity, the slurry is homogenized at a homogenization pressure of 60 MPa for 5 times;

[0267] Step S5) After homogenization, the slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0268] The finished conductive slurry containing hydrogenated nitrile rubber composite dispersant is used as the positive electrode conductive agent of the lithium ion battery cell to make the lithium ion aluminum shell battery cell. The specific method is carried out by referring to the relevant method of Example 11.

[0269] Embodiment 27

[0270] The preparation and application of a conductive paste containing a hydrogenated nitrile rubber (HNBR) composite dispersant are as follows:

[0271] Step S1) The specific surface area is 240m 2 / g carbon nanotube powder, hydrogenated nitrile rubber (HNBR) composite dispersant 7, NMP are added into the premixing tank at a ratio of CNT:HNBR:NMP=6.5:1.3:92.2, and the actual amount of NMP added is deducted from the non-solute portion of the hydrogenated nitrile rubber (HNBR) composite dispersant solution added;

[0272] Step S2) stirring at 750 rpm for 20 minutes at room temperature in a premixing tank;

[0273] Step S3) The mixed materials are pre-mixed sufficiently and then sand-milled. The linear speed of the sand-milling dispersion rotor is 15 m / s and the sand-milling is repeated 4 times.

[0274] Step S4) After the sand-grinded slurry has fluidity, the slurry is homogenized at a homogenization pressure of 100 MPa for 5 times;

[0275] Step S5) After homogenization, the slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0276] The finished conductive slurry containing hydrogenated nitrile rubber composite dispersant is used as the positive electrode conductive agent of the lithium ion battery cell to make the lithium ion aluminum shell battery cell. The specific method is carried out by referring to the relevant method of Example 11.

[0277] Embodiment 28

[0278] The preparation and application of a conductive paste containing a hydrogenated nitrile rubber (HNBR) composite dispersant are as follows:

[0279] Step S1) The specific surface area is 240m 2 / g carbon nanotube powder, hydrogenated nitrile rubber (HNBR) composite dispersant 8, and NMP are added into a premixing tank at a ratio of CNT:HNBR:NMP=6.5:1.3:92.2. The actual amount of NMP added is deducted from the non-solute portion of the hydrogenated nitrile rubber (HNBR) composite dispersant solution added;

[0280] Step S2) stirring at 750 rpm for 20 minutes at room temperature in a premixing tank;

[0281] Step S3) The mixed materials are pre-mixed sufficiently and then sand-milled. The linear speed of the sand-milling dispersion rotor is 15 m / s and the sand-milling is repeated 4 times.

[0282] Step S4) After the sand-grinded slurry has fluidity, the slurry is homogenized at a homogenization pressure of 100 MPa for 5 times;

[0283] Step S5) After homogenization, the slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0284] The finished conductive slurry containing hydrogenated nitrile rubber composite dispersant is used as the positive electrode conductive agent of the lithium ion battery cell to make the lithium ion aluminum shell battery cell. The specific method is carried out by referring to the relevant method of Example 11.

[0285] Embodiment 29

[0286] The preparation and application of a conductive paste containing a hydrogenated nitrile rubber (HNBR) composite dispersant are as follows:

[0287] Step S1) The specific surface area is 240m 2 / g carbon nanotube powder, hydrogenated nitrile rubber (HNBR) composite dispersant 9, NMP are added into the premixing tank at a ratio of CNT:HNBR:NMP=6.5:1.3:92.2, and the actual amount of NMP added is deducted from the non-solute portion of the hydrogenated nitrile rubber (HNBR) composite dispersant solution;

[0288] Step S2) stirring at 750 rpm for 20 minutes at room temperature in a premixing tank;

[0289] Step S3) The mixed materials are pre-mixed sufficiently and then sand-milled. The linear speed of the sand-milling dispersion rotor is 15 m / s and the sand-milling is repeated 4 times.

[0290] Step S4) After the sand-grinded slurry has fluidity, the slurry is homogenized at a homogenization pressure of 80 MPa for 5 times;

[0291] Step S5) After homogenization, the slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0292] The finished conductive slurry containing hydrogenated nitrile rubber composite dispersant is used as the positive electrode conductive agent of the lithium ion battery cell to make the lithium ion aluminum shell battery cell. The specific method is carried out by referring to the relevant method of Example 11.

[0293] Embodiment 30

[0294] The preparation and application of a conductive paste containing a hydrogenated nitrile rubber (HNBR) composite dispersant are as follows:

[0295] Step S1) The specific surface area is 240m 2 / g carbon nanotube powder, hydrogenated nitrile rubber (HNBR) composite dispersant 10, and NMP are added into a premixing tank at a ratio of CNT:HNBR:NMP=6.5:1.3:92.2. The actual amount of NMP added is deducted from the non-solute portion of the hydrogenated nitrile rubber (HNBR) composite dispersant solution added;

[0296] Step S2) stirring at 750 rpm for 20 minutes at room temperature in a premixing tank;

[0297] Step S3) The mixed materials are pre-mixed sufficiently and then sand-milled. The linear speed of the sand-milling dispersion rotor is 15 m / s and the sand-milling is repeated 4 times.

[0298] Step S4) After the sand-grinded slurry has fluidity, the slurry is homogenized at a homogenization pressure of 80 MPa for 5 times;

[0299] Step S5) After homogenization, the slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0300] The finished conductive slurry containing hydrogenated nitrile rubber composite dispersant is used as the positive electrode conductive agent of the lithium ion battery cell to make the lithium ion aluminum shell battery cell. The specific method is carried out by referring to the relevant method of Example 11.

[0301] Embodiment 31

[0302] The preparation and application of a conductive paste containing a hydrogenated nitrile rubber (HNBR) composite dispersant are as follows:

[0303] Step S1) The specific surface area is 320m 2 / g carbon nanotube powder, graphene, acetylene black, hydrogenated nitrile rubber (HNBR) composite dispersant 10, NMP are added into the premixing tank at a ratio of CNT: graphene: acetylene black: HNBR: NMP = 2.4: 0.8: 4.8: 2: 90, and the actual amount of NMP added is deducted from the non-solute portion of the hydrogenated nitrile rubber (HNBR) composite dispersant solution added;

[0304] Step S2) Start the premixing tank for high and low speed stirring, the high speed stirring speed is 1100 rpm, and after premixing for 20 minutes,

[0305] Step S3) The mixed materials are pre-mixed sufficiently and then sand-milled. The linear speed of the sand-milling dispersion rotor is 15 m / s and the sand-milling is repeated 4 times.

[0306] Step S4) After the sand-grinded slurry has fluidity, the slurry is homogenized at a homogenization pressure of 80 MPa for 5 times;

[0307] Step S5) After homogenization, the slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0308] The finished conductive slurry containing hydrogenated nitrile rubber composite dispersant is used as the positive electrode conductive agent of the lithium ion battery cell to make the lithium ion aluminum shell battery cell. The specific method is carried out by referring to the relevant method of Example 11.

[0309] Embodiment 32

[0310] The preparation and application of a conductive paste containing a hydrogenated nitrile rubber (HNBR) composite dispersant are as follows:

[0311] Step S1) The specific surface area is 320m 2 / g carbon nanotube powder, Ketjen black, hydrogenated nitrile rubber (HNBR) composite dispersant 10, and NMP are added into a premixing tank at a ratio of CNT: Ketjen black: HNBR: NMP = 2.5: 5.5: 2: 90. The actual amount of NMP added is deducted from the non-solvent portion of the hydrogenated nitrile rubber (HNBR) composite dispersant solution.

[0312] Step S2) Start the premixing tank for high and low speed stirring, the high speed stirring speed is 1100 rpm, and after premixing for 20 minutes,

[0313] Step S3) The mixed materials are pre-mixed sufficiently and then sand-milled. The linear speed of the sand-milling dispersion rotor is 15 m / s and the sand-milling is repeated 4 times.

[0314] Step S4) After the sand-grinded slurry has fluidity, the slurry is homogenized at a homogenization pressure of 80 MPa for 5 times;

[0315] Step S5) After homogenization, the slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0316] The finished conductive slurry containing hydrogenated nitrile rubber composite dispersant is used as the positive electrode conductive agent of the lithium ion battery cell to make the lithium ion aluminum shell battery cell. The specific method is carried out by referring to the relevant method of Example 11.

[0317] Embodiment 33

[0318] The preparation and application of a conductive paste containing a hydrogenated nitrile rubber (HNBR) composite dispersant are as follows:

[0319] Step S1) The specific surface area is 320m 2 / g carbon nanotube powder, acetylene black, hydrogenated nitrile rubber (HNBR) composite dispersant 10, NMP are added into the premixing tank at a ratio of CNT: acetylene black: HNBR: NMP = 2.5: 5.5: 2: 90, and the actual amount of NMP added is deducted from the non-solute portion of the hydrogenated nitrile rubber (HNBR) composite dispersant solution added;

[0320] Step S2) Start the premixing tank for high and low speed stirring, the high speed stirring speed is 1100 rpm, and after premixing for 20 minutes,

[0321] Step S3) The mixed materials are pre-mixed sufficiently and then sand-milled. The linear speed of the sand-milling dispersion rotor is 15 m / s and the sand-milling is repeated 4 times.

[0322] Step S4) After the sand-grinded slurry has fluidity, the slurry is homogenized at a homogenization pressure of 80 MPa for 5 times;

[0323] Step S5) After homogenization, the slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0324] The finished conductive slurry containing hydrogenated nitrile rubber composite dispersant is used as the positive electrode conductive agent of the lithium ion battery cell to make the lithium ion aluminum shell battery cell. The specific method is carried out by referring to the relevant method of Example 11.

[0325] Embodiment 34

[0326] The preparation and application of a conductive paste containing a hydrogenated nitrile rubber (HNBR) composite dispersant are as follows:

[0327] Step S1) The specific surface area is 320m 2 / g carbon nanotube powder, conductive carbon black SP, hydrogenated nitrile rubber (HNBR) composite dispersant 10, NMP are added into the premixing tank at a ratio of CNT: conductive carbon black SP: HNBR: NMP = 2.5: 5.5: 2: 90, and the actual amount of NMP added is deducted from the non-solute portion of the hydrogenated nitrile rubber (HNBR) composite dispersant solution added;

[0328] Step S2) Start the premixing tank for high and low speed stirring, the high speed stirring speed is 1100 rpm, and after premixing for 20 minutes,

[0329] Step S3) The mixed materials are pre-mixed sufficiently and then sand-milled. The linear speed of the sand-milling dispersion rotor is 15 m / s and the sand-milling is repeated 4 times.

[0330] Step S4) After the sand-grinded slurry has fluidity, the slurry is homogenized at a homogenization pressure of 80 MPa for 5 times;

[0331] Step S5) After homogenization, the slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0332] The finished conductive slurry containing hydrogenated nitrile rubber composite dispersant is used as the positive electrode conductive agent of the lithium ion battery cell to make the lithium ion aluminum shell battery cell. The specific method is carried out by referring to the relevant method of Example 11.

[0333] Embodiment 35

[0334] The preparation and application of a conductive paste containing a hydrogenated nitrile rubber (HNBR) composite dispersant are as follows:

[0335] Step S1) The specific surface area is 320m 2 / g carbon nanotube powder, graphene, hydrogenated nitrile rubber (HNBR) composite dispersant 10, NMP are added into the premixing tank at a ratio of CNT: graphene: HNBR: NMP = 3.25: 1.75: 1: 94, and the actual amount of NMP added is deducted from the non-solute portion of the hydrogenated nitrile rubber (HNBR) composite dispersant solution;

[0336] Step S2) Start the premixing tank for high and low speed stirring, the high speed stirring speed is 1100 rpm, and after premixing for 20 minutes,

[0337] Step S3) The mixed materials are pre-mixed sufficiently and then sand-milled. The linear speed of the sand-milling dispersion rotor is 15 m / s and the sand-milling is repeated 4 times.

[0338] Step S4) After the sand-grinded slurry has fluidity, the slurry is homogenized at a homogenization pressure of 80 MPa for 5 times;

[0339] Step S5) After homogenization, the slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0340] The finished conductive slurry containing hydrogenated nitrile rubber composite dispersant is used as the positive electrode conductive agent of the lithium ion battery cell to make the lithium ion aluminum shell battery cell. The specific method is carried out by referring to the relevant method of Example 11.

[0341] Comparative Example 1

[0342] A preparation and application of a conductive paste, the steps are as follows:

[0343] Step 1) The specific surface area is 320m 2 / g carbon nanotube powder, PVP, additives, and NMP are added and premixed in a premixing tank at a ratio of CNT:PVP: additives:NMP=3.2:0.8:0.5:95.5;

[0344] Step 2) sand-milling the pre-mixed conductive slurry 10 times;

[0345] Step 3) The sand-milled slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0346] The finished conductive paste is used as the positive electrode conductive agent of the lithium-ion battery to make the lithium-ion aluminum shell battery. The specific method is carried out by referring to the relevant method of Example 11.

[0347] Comparative Example 2

[0348] A preparation and application of a conductive paste, the steps are as follows:

[0349] Step 1) The specific surface area is 240m 2 / g carbon nanotube powder, PVP, additives, and NMP are added and premixed in a premixing tank at a ratio of CNT:PVP: additives:NMP=5:1:0.3:93.7;

[0350] Step 2) sand-milling the pre-mixed conductive slurry 10 times;

[0351] Step 3) The sand-milled slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0352] The finished conductive paste is used as the positive electrode conductive agent of the lithium-ion battery to make the lithium-ion aluminum shell battery. The specific method is carried out by referring to the relevant method of Example 11.

[0353] Comparative Example 3

[0354] A preparation and application of a conductive paste, the steps are as follows:

[0355] Step 1) The specific surface area is 320m2 / g carbon nanotube powder, graphene, acetylene black, PVP, and NMP are added and premixed in a premixing tank at a ratio of CNT: graphene: acetylene black: PVP: NMP = 2.4: 0.8: 4.8: 2: 90;

[0356] Step 2) sand-milling the pre-mixed conductive slurry 10 times;

[0357] Step 3) The sand-milled slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0358] The finished conductive paste is used as the positive electrode conductive agent of the lithium-ion battery to make the lithium-ion aluminum shell battery. The specific method is carried out by referring to the relevant method of Example 11.

[0359] Comparative Example 4

[0360] A preparation and application of a conductive paste, the steps are as follows:

[0361] Step 1) The specific surface area is 320m 2 / g carbon nanotube powder, Ketjen black, PVP, and NMP are added and premixed in a premixing tank at a ratio of CNT: Ketjen black: PVP: NMP = 2.5:5.5:2:90;

[0362] Step 2) sand-milling the pre-mixed conductive slurry 10 times;

[0363] Step 3) The sand-milled slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0364] The finished conductive paste is used as the positive electrode conductive agent of the lithium-ion battery to make the lithium-ion aluminum shell battery. The specific method is carried out by referring to the relevant method of Example 11.

[0365] Comparative Example 5

[0366] A preparation and application of a conductive paste, the steps are as follows:

[0367] Step 1) The specific surface area is 320m 2 / g carbon nanotube powder, acetylene black, PVP, and NMP are added into a premixing tank at a ratio of CNT: acetylene black: PVP: NMP = 2.5: 5.5: 2: 90;

[0368] Step 2) sand-milling the pre-mixed conductive slurry 10 times;

[0369] Step 3) The sand-milled slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0370] The finished conductive paste is used as the positive electrode conductive agent of the lithium-ion battery to make the lithium-ion aluminum shell battery. The specific method is carried out by referring to the relevant method of Example 11.

[0371] Comparative Example 6

[0372] A preparation and application of a conductive paste, the steps are as follows:

[0373] Step 1) The specific surface area is 320m 2 / g carbon nanotube powder, conductive carbon black SP, PVP, and NMP are added and premixed in a premixing tank at a ratio of CNT: conductive carbon black SP: PVP: NMP = 2.5: 5.5: 2: 90;

[0374] Step 2) sand-milling the pre-mixed conductive slurry 10 times;

[0375] Step 3) The sand-milled slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0376] The finished conductive paste is used as the positive electrode conductive agent of the lithium-ion battery to make the lithium-ion aluminum shell battery. The specific method is carried out by referring to the relevant method of Example 11.

[0377] Comparative Example 7

[0378] A preparation and application of a conductive paste, the steps are as follows:

[0379] Step 1) The specific surface area is 320m 2 / g carbon nanotube powder, graphene, PVP, and NMP are added and premixed in a premixing tank at a ratio of CNT: graphene: PVP: NMP = 3.25: 1.75: 1: 94;

[0380] Step 2) sand-milling the pre-mixed conductive slurry 10 times;

[0381] Step 3) The sand-milled slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0382] The finished conductive paste is used as the positive electrode conductive agent of the lithium-ion battery to make the lithium-ion aluminum shell battery. The specific method is carried out by referring to the relevant method of Example 11.

[0383] The electrode sheet resistivity, slurry viscosity stability and battery cell internal resistance of Example 11 to Example 20 were compared with Comparative Example 1.

[0384] The electrode sheet resistivity, slurry viscosity stability, and battery cell internal resistance were compared and tested between Examples 21 to 30 and Comparative Example 2.

[0385] Example 31 and Comparative Example 3, Example 32 and Comparative Example 4, Example 33 and Comparative Example 5, Example 34 and Comparative Example 6, and Example 35 and Comparative Example 7 were tested for electrode sheet resistivity, slurry viscosity stability, and battery cell internal resistance.

[0386]

[0387]

[0388] By comparison, it can be found that the electrode sheet resistivity of the conductive paste prepared by the present invention is 40%-60% lower than that of the comparative example, the internal resistance of the battery cell is -5% lower, and the low-temperature DCR is -10% lower, so the conductive paste has better conductivity and more stable viscosity.

[0389] Embodiment 36

[0390] The preparation method of hydrogenated nitrile rubber dispersant solution is:

[0391] Step 1) selecting hydrogenated nitrile rubber with a mass average molecular weight of 200,000 and cutting it into small pieces of 8 cubic centimeters in volume using a rubber cutting machine;

[0392] Step 2) HNBR, NMP and additives cut into small pieces are mixed in a mass ratio of 10:85:5, added to a stirring tank, and HNBR is immersed in the liquid at 25°C for 2 hours; the additive is C2020 polyether polyol, Pl L64 polyether surfactant and D-aminopropanol are combined in a mass ratio of 1:0.5:0.5;

[0393] Step 3) stirring the mixture after step 2 at 25°C and 500 rpm for 8 hours;

[0394] Step 4) homogenizing the mixed material after step 3, at 40° C. and a homogenization pressure of 110 MPa, for 5 times to obtain a hydrogenated nitrile rubber composite dispersant solution;

[0395] Step 5) demagnetizing the hydrogenated nitrile rubber composite dispersant solution after step 4, controlling the magnetic intensity of the permanent magnet demagnetization to 15000 Gauss, to obtain a hydrogenated nitrile rubber composite dispersant solution;

[0396] Step 6) The hydrogenated nitrile rubber composite dispersant solution is sealed and canned to obtain a finished solution, which is recorded as a hydrogenated nitrile rubber composite dispersant.

[0397] The preparation method of the conductive paste is as follows:

[0398] Step S1) The specific surface area is 240m 2 / g carbon nanotube powder, hydrogenated nitrile rubber composite dispersant and NMP are mixed, wherein the mass ratio of CNT:HNBR:NMP=6.5:1.3:92.2 is effectively controlled, and the materials are added into the premixing tank, and the actual amount of NMP added is deducted from the non-solute part of the amount of hydrogenated nitrile rubber composite dispersant solution added;

[0399] Step S2) stirring at 750 rpm for 20 minutes at room temperature in a premixing tank;

[0400] Step S3) The mixed materials are pre-mixed sufficiently and then sand-milled. The linear speed of the sand-milling dispersion rotor is 15 m / s and the sand-milling is repeated 4 times.

[0401] Step S4) After the sand-grinded slurry has fluidity, the slurry is homogenized at a homogenization pressure of 80 MPa for 5 times;

[0402] Step S5) After homogenization, the slurry is demagnetized by a permanent magnet with a magnetic strength of 10,000 Gauss to obtain a finished conductive slurry;

[0403] The finished conductive slurry containing hydrogenated nitrile rubber composite dispersant is used as the positive electrode conductive agent of the lithium ion battery cell to make the lithium ion aluminum shell battery cell. The specific method is carried out by referring to the relevant method of Example 11.

[0404] Embodiment 37

[0405] The difference from Example 36 is that the auxiliary agent is C2020 polyether polyol, F68 polyether surfactant and D-aminopropanol are combined in a mass ratio of 1:0.5:0.5.

[0406] Embodiment 38

[0407] The difference from Example 36 is that the auxiliary agent is C2020 polyether polyol, nonylphenol polyoxyethylene ether TX-10 and D-aminopropanol are combined in a mass ratio of 1:0.5:0.5.

[0408] Comparative Example 8

[0409] The difference from Example 36 is that the auxiliary agent is C2020 polyether polyol L64 polyether surfactant is combined in a mass ratio of 1:1.

[0410]

[0411] From the perspective of the electrode resistivity, Example 36 has the lowest value, indicating that its conductive network is more complete and the internal loss of the electrode is smaller; Example 37 is slightly inferior but still better than the benchmark Example 23, and Example 38 is slightly worse than the benchmark; Comparative Example 8 is the highest, showing that the conductive agent has the worst dispersion ability. In terms of slurry viscosity, Examples 36 and 37 are significantly lower than Benchmark 23 after discharge and storage for two months, and the viscosity growth rate is smaller; Example 38 is slightly higher; Comparative Example 8 has a sharp increase in viscosity after storage, which can easily lead to unstable coating and agglomeration. The internal resistance of the battery cell and low-temperature DCR also show similar trends: Example 36 maintains a relatively low internal resistance at room temperature and -10°C, Example 37 follows closely and performs better than Benchmark 23, and Example 38 is equivalent to or slightly worse than the benchmark; Comparative Example 8 performs the weakest, indicating that its dispersion and bonding effects are obviously insufficient.

[0412] The polyether polyol, polyether surfactant and D-aminopropanol of the present invention further form a synergistic effect. The polyether polyol plays a role in wetting the matrix between the solvent and the hydrogenated nitrile rubber, reducing the aggregation between the macromolecular chains; the polyether surfactant greatly reduces the interfacial tension through the block PEO / PPO structure, forms a tight shell on the surface of the conductive particles, and inhibits secondary agglomeration; and the amine group of D-aminopropanol can form stronger hydrogen bonds or ion couplings with HNBR and polyether molecular chains, and produce multi-point anchoring on the surface of high specific surface area carbon materials. Test data show that the embodiments using the ternary combination (such as embodiments 36 and 37) are superior to the benchmark or comparative examples in terms of electrode resistivity, slurry viscosity (including rebound after storage), battery cell internal resistance, low-temperature DCR, etc., and the combined effect has a significant enhancement effect on dispersion stability and the construction of a conductive network.

Claims

1. A hydrogenated nitrile rubber dispersant solution, comprising a solute, a solvent and an auxiliary agent, characterized in that: The solute is hydrogenated nitrile rubber; The solvent is N-methylpyrrolidone; The auxiliary agent is an organic alcohol amine compound.

2. The hydrogenated nitrile rubber dispersant solution according to claim 1, wherein Calculated by mass percentage, it consists of 1-30% hydrogenated nitrile rubber, 0.1-15% auxiliary agent and the balance is N-methylpyrrolidone.

3. The hydrogenated nitrile rubber dispersant solution as claimed in claim 2, characterized in that Calculated by mass percentage, it consists of 8-20% hydrogenated nitrile rubber, 3-10% auxiliary agent and the balance is N-methylpyrrolidone.

4. The hydrogenated nitrile rubber dispersant solution according to any one of claims 1 to 3, characterized in that The auxiliary agent is a combination of polyether polyol and D-aminopropanol in a mass ratio of 1:(0.2-5).

5. The method for preparing a hydrogenated nitrile rubber dispersant solution according to any one of claims 1 to 4, characterized in that: The steps include: Mixing hydrogenated nitrile rubber, N-methylpyrrolidone and an additive; High pressure homogenization.

6. The method for preparing a hydrogenated nitrile rubber dispersant solution as claimed in claim 5, characterized in that: The steps include: S1) cutting hydrogenated nitrile rubber into pieces with a rubber cutting machine; S2) adding the chopped hydrogenated nitrile rubber, N-methylpyrrolidone and additives into a stirring tank in proportion, and soaking at 20-28° C. for 1-3 hours; S3) stirring at 20-28° C. and 200-1000 rpm for 6-10 hours; S4) homogenize at 20-50℃ and pressure 40-180MPa for 2-8 times; S5) Demagnetization.

7. A conductive paste, characterized in that: The method comprises a conductive agent, a hydrogenated nitrile rubber dispersant solution as claimed in any one of claims 1 to 4, and N-methylpyrrolidone.

8. The conductive paste according to claim 7, characterized in that: The mass content of the conductive agent in the conductive paste is 1.5-15%, and the mass content of the hydrogenated nitrile rubber is 0.2-4%.

9. The method for preparing the conductive paste according to claim 7 or 8, characterized in that: The steps include: a) stirring the conductive agent, the hydrogenated nitrile rubber dispersant solution and N-methylpyrrolidone in a premixing tank at 200-1000 rpm for 10-30 min; b) Sanding, homogenization or ultrasound.

10. Use of the conductive paste according to claim 7 or 8 in lithium battery electrodes.